Kontribusi Kiai Shaleh Darat dalam Penulisan Tafsir di Indonesia - Istianah, Istianah (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2018)
This article discusses the contribution of Kiai Shaleh Darat, a prominent Muslim scholar as well as a noticeable warrior against Western invaders, in writing Qur’anic commentaries in Indonesia. His Qur’anic commentary entitled Fayd al-Rahman fi Tarjamat Tafsir Kalam Malik al-Dayyan, written in Javanese-Arabic (pegon), is not only considered as a representation of Javanese identity, but also as a means of resistance against Dutch colonialism. Through interpretation, he is not only giving an understanding of the Qur’an, but also managing a resistance through the Qur’anic exegesis. That is because at that time the Dutch government forbade the translation of the Qur’an. This interpretation is written using the method of tahlili (explanation) with Sufis nuance which becomes the spirit in each word of his interpretation. Shaleh Darat was greatly influenced by Sufism figures such as Imam al-Ghazali through his Ihya’ ‘Ulum al-Din and Ibn ‘Ata’illah through his Hikam. Thi article eventually argues that Fayd al-Rahman has, at least, three contributive manifestations in the discourse of Indonesia Qur’anic interpretation: the Qur’anic sufism, cultural resistance, and community development in instilling the values of goodness.